A Compartive Study on the Effect of Gamma-irradiation on Growth and Biomass Yield in Certain Fuel-wood Species - Bandyopadhyay, Bandana; Nandy, A. K.; Mallick, R.; Chatterjee, A. (Indian Forester, 1990)
A trial was conducted to study a comparative effect of Gamma-radiation on the growth behaviour vis-a-vis biomass yield of Acacia nilotica Delite, Leucaena leucocephala (Lam) De Wit and Prosopis chilensis D.C (sub-family Mimosoidae). Dry seeds were exposed to 1, 2, 4, 8 and 16 KR doses of Gamma-radiation. Irradiated seeds were sown in the field along with the control. In case of L. leucocephala the growth of the plants as well as total biomass production increased steadily with increasing doses of irradiation upto 8 KR. In A. nilotica the response was similar to that of L leucocephala, but in this case maximum growth and biomass yield was obtained after 4 KR. On the other hand, P. chilensis did not exhibit a positive response to Gamma-radiation. Karyotype of the three species was also done. All these observations indicate the greater possibility of the utilization of Gamma-radiation in increasing biomass production.